Influence of dietary fat source and feeding duration on finishing pig growth performance, carcass composition, and fat quality - Stephenson, Ethan W.; Vaughn, M. A.; Burnett, D. D.; Paulk, C. B.; Tokach, Michael D.; Dritz, Steven S.; DeRouchey, Joel M.; Goodband, Robert D.; Woodworth, Jason C.; Gonzalez, John M. (My University, 2017)
A total of 160 finishing pigs (PIC 327 × 1050; initially 45.6 kg) were used in an 84-d experiment to evaluate the effects of dietary fat source and feeding duration on growth performance, carcass characteristics, and carcass fat quality. There were 2 pigs per pen with 8 pens per treatment. The 10 dietary treatments were a corn–soybean meal control diet with no added fat and a 3 × 3 factorial with main effects of fat source (4% tallow, 4% soybean oil, or a blend of 2% tallow and 2% soybean oil) and feeding duration (d 0 to 42, 42 to 84, or 0 to 84). The control corn– soybean meal diet was fed in place of added fat diets when needed for duration treatment purposes. On d 0, 1 pig was identified in each pen and fat biopsy samples of the back, belly, and jowl were collected on d 0, 41, and 81 for fatty acid analysis. At the conclusion of the study, all pigs were harvested, carcass characteristics were determined, and back, belly, and jowl fat samples were collected for analysis. Overall (d 0 to 84), there were no differences among pigs fed the different fat sources for growth and carcass characteristics; however, pigs fed diets with added fat for the entire study had improved (P = 0.036) G:F compared with pigs fed the control diet without added fat. Pigs fed supplemental fat throughout the entire study also had improved (P < 0.05) ADG and G:F as well as heavier d-84 BW (P = 0.006) compared with pigs fed additional fat during only 1 period. Adding fat for the entire study increased (P = 0.032) backfat and tended to reduce (P = 0.079) the fat free lean index compared with pigs fed the control diet without added fat. Added fat also increased (P < 0.05) the iodine value (IV) when compared with pigs fed the control diet. Increasing the feeding duration of soybean oil lowered MUFA and increased PUFA concentrations for all fat depots, whereas these values remained relatively unchanged by the addition of tallow (duration × fat source interactions, P < 0.05). Our study failed to show any feeding period × fat source interactions (P < 0.05) in fatty acid composition or IV for jowl fat, whereas this interaction occurred for belly fat and backfat, which would indicate a longer turnover rate for jowl fat. In conclusion, feeding additional fat improved ADG and G:F; however, feeding soybean oil for an increased duration, either alone or in combination with tallow, negatively affected the fatty acid composition and IV of different fat depots. © 2016 American Society of Animal Science. All rights reserved.
Citation: Stephenson, E. W., Vaughn, M. A., Burnett, D. D., Paulk, C. B., Tokach, M. D., Dritz, S. S., . . . Gonzalez, J. M. (2016). Influence of dietary fat source and feeding duration on finishing pig growth performance, carcass composition, and fat quality. Journal of Animal Science, 94(7), 2851-2866. doi:10.2527/jas2015-9521
Keywords: Carcass; Finishing Pig; Growth; Iodine Value; Soybean Oil; Tallow